2011
DOI: 10.3109/15513815.2011.572962
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyomatous Hamartoma of the Popliteal Lymph Nodes in a Patient with Klippel-Trenaunay Syndrome: Case Report

Abstract: We present a case of angiomyomatous hamartoma (AMH) in the popliteal region of a patient with Klippel-Trenaunay syndrome. A 14-year-old boy with a right popliteal mass and recurrent edema of the right leg was admitted to a local hospital where a diagnosis of Klippel-Trenaunay syndrome was made. Three lymph nodes in the right popliteal fossa were removed. Histopathologic examination showed angiomyomatous hamartomas. Postoperatively, the patient was followed for 6 years. He had occasional mild edema of the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It prevalently involves inguinal lymph nodes, appearently starting in the hilum and extending towards the cortex. This entity was first described by Chan et al in 1992, and, so far, 28 cases have been reported in the literature [9-11,14-23]. Table 1 shows age, gender and location of the lesion in 28 patients.…”
Section: Discussionmentioning
confidence: 97%
“…It prevalently involves inguinal lymph nodes, appearently starting in the hilum and extending towards the cortex. This entity was first described by Chan et al in 1992, and, so far, 28 cases have been reported in the literature [9-11,14-23]. Table 1 shows age, gender and location of the lesion in 28 patients.…”
Section: Discussionmentioning
confidence: 97%
“…[ 1 ] in 1992 as a distinctive vascular hamartomatous lesion that primarily occurs in inguinal and femoral lymph nodes [ 2 , 3 ]. Occasional cases have been reported in popliteal and cervical lymph nodes [ 4 , 5 ]. Patients may present with painless or painful swelling [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiomyomatous hamartoma (AMH) of the lymph node is characterized by partial replacement of normal nodal parenchyma by disorganized blood vessels and smooth muscle cells with or without adipose tissue within a fibrous stroma. Inguinal and femoral lymph nodes are commonly involved [ 1 - 3 ], while popliteal lymph node involvement is uncommon [ 4 , 5 ]. We report a rare case of AMH of the popliteal lymph node in a young patient with a clinical diagnosis of Baker’s cyst.…”
mentioning
confidence: 99%
“…Patient median age 42 (ages 8 months to 82 years, standard deviation of 21), with a male-to-female ratio of 5:2. The disease mainly affected the inguinal and femoral lymph nodes, [1,[3][4][5][6][7][8][9] although there are three reports of cervical lymph node involvement [10][11][12] and two of popliteal lymph node involvement [13,14]. It usually presented as a painless, unilateral inguinal lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only 28 cases of AMH of a lymph node have been reported in the literature (Table 1) [1,[3][4][5][6][7][8][9][10][11][12][13][14]. Patient median age 42 (ages 8 months to 82 years, standard deviation of 21), with a male-to-female ratio of 5:2.…”
Section: Introductionmentioning
confidence: 99%